Contrasting patterns of naturalized plant richness in the Americas: Numbers are higher in the North but expected to rise sharply in the South - Petr Pyšek; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Hanno Seebens; Mark van Kleunen; Patrick Weigelt; Marten Winter (Global Ecology and Biogeography, 2019)
With increasing availability of plant distribution data, the information about global plant diversity is improving rapidly. Recently, Ulloa Ulloa et al. (2017) presented the first comprehensive overview of the native vascular flora of the Americas, yielding a total count of 124,993 native species. Of these, 51,241 occur in North America and 82,052 in South America. By combining these data with the information in the Global Naturalized Alien Flora (GloNAF) database of naturalized alien floras, we point out that for a complete picture of the regional and continental plant richness, the naturalized alien species need to be considered. Ignoring this novel component of regional floras can lead to an inaccurate picture of overall change in biodiversity in the Anthropocene. We show that North and South America might face contrasting challenges in terms of potential threats to biodiversity posed by alien plant species, because of the different past and present dynamics of invasions and predictions of future development. In total, there are 7,042 naturalized alien plants occurring in the Americas, with 6,122 recorded in North America and 2,677 in South America; if only introductions from other continents are considered additions to the native continental flora make up 6.9 and 1.4 %, respectively. Nevertheless, predictions of naturalized plant trajectories based on global trade dynamics and climate change suggest that considerable increases in naturalized plant numbers are expected in the next 20 years for emerging South American economies, which could reverse the present state.